Carcass traits of two marketable size classes of Pangasius pangasius (Hamilton, 1822). (20th August 2012) - Sahu, B. B.; Sahoo, S. K.; Giri, S. S.; Das, P. C.; Mishra, B.; Sahu, A. K.; Eknath, A. E.; Jayasankar, P.
Summary Carcass and commercial yield traits of Pangasius pangasius were evaluated and morphometric parameters measured along with carcass traits in two marketable weight classes (average ± SD) 1603 ± 49.5 g and 1985.6 ± 56.6 g. The Pangas fish head yield was 14.80% and 15.1% for the 2000 g and 1600 g weight classes, respectively. The offal percentage varied from 8.6 to 8.8 in both weight classes. Pangasius had a significant accumulation of fat deposits in mesenteric tissue and on the lining of the abdominal cavity. Headless (73.2%), head and skinless (68.7%), head, skin and boneless (57.7%) dressing yields were significantly higher in 1600 g than in the 2000 g weight class. The 2000 g weight class category exhibited mesenteric fat (4.3%), dissected subcutaneous and intramuscular fat (10.1%) which was significantly higher than in the 1600 g weight class. The yields of dressing stages were affected mostly by skin (8.3–4.5%) and mesenteric fat (4.3–3.7%), and dissected subcutaneous and intramuscular fat (10.1–6.8%), which is significantly higher in the 2000 g than in the 1600 g category. The later weight class category resulted in more meat yield, and less bone, skin and fat yields.